2020
DOI: 10.1111/pbi.13364
|View full text |Cite
|
Sign up to set email alerts
|

Turning a green alga red: engineering astaxanthin biosynthesis by intragenic pseudogene revival in Chlamydomonas reinhardtii

Abstract: Summary The green alga Chlamydomonas reinhardtii does not synthesize high‐value ketocarotenoids like canthaxanthin and astaxanthin; however, a β‐carotene ketolase (CrBKT) can be found in its genome. CrBKT is poorly expressed, contains a long C‐terminal extension not found in homologues and likely represents a pseudogene in this alga. Here, we used synthetic redesign of this gene to enable its constitutive overexpression from the nuclear genome of C. reinhardtii. Overexpression of the optimized CrBKT extended n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 89 publications
3
93
0
Order By: Relevance
“…The gradual distribution of expression levels observed across this intron set hinders generalizations of the degree of IME that can be expected from different intron sequences. The first intron (i1) of RBCS2 has been reported across multiple studies to be a reliable and strong IME effecting intron for C. reinhardtii nuclear transgene expression [31][32][33][39][40][41][42][43]. In this study, higher IME was observed from the introns natively located in closer proximity to the respective promoter, however, with some exceptions (ACTIN, LHCBM1, RPS8, LHCBM3, and RPL20, S1 Fig).…”
Section: Plos Geneticsmentioning
confidence: 54%
See 2 more Smart Citations
“…The gradual distribution of expression levels observed across this intron set hinders generalizations of the degree of IME that can be expected from different intron sequences. The first intron (i1) of RBCS2 has been reported across multiple studies to be a reliable and strong IME effecting intron for C. reinhardtii nuclear transgene expression [31][32][33][39][40][41][42][43]. In this study, higher IME was observed from the introns natively located in closer proximity to the respective promoter, however, with some exceptions (ACTIN, LHCBM1, RPS8, LHCBM3, and RPL20, S1 Fig).…”
Section: Plos Geneticsmentioning
confidence: 54%
“…frequently used for biotechnological studies aimed at metabolic engineering and recombinant protein expression in C. reinhardtii [31,[39][40][41][42][43][44]79]. Here, we identified several intron sequences that induce strong IME comparable or even higher than RBCS2i1 (Fig 1).…”
Section: Plos Geneticsmentioning
confidence: 82%
See 1 more Smart Citation
“…The authors attributed this finding to the enzyme's inaccessibility to its substrate ß-carotene. In a more recent publication, Perozeni et al 20 also attempted to overexpress CrBKT in Chlamydomonas npq2 mutant, but their study differs from ours. They directed CrBKT to the thylakoid membrane via fusion of the psaD chloroplast transit peptide (cTP 53 ) to its N-terminus.…”
Section: Discussionmentioning
confidence: 67%
“…As a result, both astaxanthin and canthaxanthin are detected in their psaD-CrBKT transformants. In our study, we intentionally did not include cTP because there is evidence of an intrinsic cTP in CrBKT sequence, both from in silico sequence analysis with PredAlgo 54 as well as fluorescence translocation assay 20 . The lack of astaxanthin leads to the assumption that CrBKT was expressed and imported into chloroplast but not into thylakoid membrane, thus leaving it unable to metabolize zeaxanthin.…”
Section: Discussionmentioning
confidence: 99%